Study of the SARS-CoV-2-specific immune T-cell responses in COVID-19-positive cancer patients. (June 2021) - Mansi, Laura; Spehner, Laurie; Daguindau, Etienne; Bouiller, Kevin; Almotlak, Hamadi; Stein, Ulrich; Bouard, Adeline; Kim, Stefano; Klajer, Elodie; Jary, Marine; Meynard, Guillaume; Vienot, Angélique; et al.
Abstract: Background: Cancer patients are considered highly vulnerable to the COVID-19 pandemic. However, delaying cancer-specific therapies could have a deleterious effect on survival. The potential suppressive effects of chemotherapies or cancer-related microenvironment raised the question on how cancer patients' immune system responds to SARS-CoV-2 virus. Methods: We have started a prospective monocentric trial entitled COV-CREM (NCT04365322) in April 2020. The primary objective of the trial was to assess specific immune response's intensity and diversity to SARS-CoV-2 in infected patients. Results: In this study, we showed that cancer patients (28 solid tumours, 11 haematological malignancies) exposed to SARS-CoV-2 produced a high rate of specific antibodies, as observed in patients without a cancer history (n = 29). However, our results highlight a lack in the generation of T-cell responses against CoV–N, M and S proteins from the SARS-CoV-2 virus, suggesting that cancer patients failed to mount a protective T-cell immunity. Nevertheless, SARS-CoV-2 infection did not impair established immune memory since specific responses against common viruses were not hampered in cancer patients. Conclusion: Given the severity and the unknown evolution of the ongoing COVID-19 pandemic, it is of fundamental importance to integrate cancer patients in vaccination programs. Highlights: Adaptive T-cell immunity targeting SARS-CoV-2 is weak in cancer patients. COVID-19 infection does not alter the common virus's memory-T-cell responses. Immunoglobulin monitoring is not sufficient to characterise infection's immunity. Specific T-cell responses monitoring should be developed in the vaccination program.